Clinical and Biomedical Research - Zavascki, Alexandre P. (Clinical and Biomedical Research, 2014)
I am very pleased to introduce to researchers, medical and all healthcare-associated professionals, and to all readers potentially interested in the field, the first issue of the scientific journal Clinical and Biomedical Research (CBR). CBR is the former Revista HCPA, a 33 year-old scientific publication of Hospital de Clínicas de Porto Alegre and Universidade Federal do Rio Grande do Sul that is now largely reformulated in order to reach a broader range of readers and researchers.